Polyploidy – A tool in adapting trees to future climate changes? A review of polyploidy in trees - Ræbild, Anders; Anamthawat-Jónsson, Kesara; Egertsdotter, Ulrika; Immanen, Juha; Jensen, Anna Monrad; Koutouleas, Athina; Martens, Helle Jakobe; Nieminen, Kaisa; Olofsson, Jill Katharina; Röper, Anna-Catharina; Salojärvi, Jarkko; Strömvik, Martina; et al. (Elsevier, 2024)
Polyploidy, or genome doubling, has occurred repeatedly through plant evolution. While polyploid plants are used extensively in agriculture and horticulture, they have so far found limited use in forestry. Here we review the potentials of polyploid trees under climate change, and investigate if there is support for increased use. We find that polyploid trees like other plants have consistent increases in cell sizes compared to diploids, and that leaf-area based rates of photosynthesis tend to increase with increasing levels of ploidy. While no particular trend could be discerned in terms of biomass between trees of different ploidy levels, physiology is affected by polyploidization and several studies point towards a high potential for polyploid trees to adapt to drought stress. The ploidy level of most tree species is unknown, and analysis of geographical patterns in frequencies of polyploid trees are inconclusive. Artificial polyploid trees are often created by colchicine and in a few cases these have been successfully applied in forestry, but the effects of induced polyploidization in many economically important tree species remains untested. Polyploids would also be increasingly useful in tree breeding programs, to create synthetic hybrids or sterile triploids that could control unwanted spreading of germplasm in nature. In conclusion, this review suggests that polyploid trees may be superior under climate change in some cases, but that the potential of polyploids is not yet fully known and should be evaluated on a case-to-case basis for different tree species.
Keywords: adaptation; ecophysiology; fitness; forestry; tree breeding; whole genome duplication (WGD)